EXAMINING THE RELATIONSHIP BETWEEN PRESCHOOL CHILDREN’S SELF-REGULATION SKILLS AND PARENTAL ATTITUDES - Kübra EKE (International Journal of Eurasia Social Sciences, 2017)
Self-regulation skills, defined as the ability to direct or control an individual’s emotions, thoughts, attentions and actions, are skills that are important in the first years of life and are effective in the attainment of the attitude of parents. For this reason, this research aims to investigate the relationship between pre-school children’s self-regulation skills and parental attitudes. The main hypothesis of the research is that different parental attitudes have a significant and important role in determining the quality and qualification of self-regulation skills. The study group of the study consists of 130 children and their mothers who are in pre-school education in the province of Ankara during the academic year 2016-2017. In order to collect data in the survey; "Demographic Information Form", "Parent Attitude Scale" and "Self-Regulation Skills Scale". Percentage, frequency, average, t test, one way variance analysis (ANOVA) and correlation analysis were used in the analysis step of the study. As a result of the data obtained from the data collection tools, there was a significant relationship between the self-regulation skills of the children and the parents’ permissive attitudes and no significant relationship was found between democratic, authoritarian and protective attitudes. In addition, the self-regulation skills of the children did not differ any difference according to gender, age, birth order, and the income level of the family showed a significant difference according to the number of siblings, mother’s age and mother’s working status.